Mechanical circulatory support systems: evolution, the systems and outlook - Hetzer, Roland (Cardiovasc Diagn Ther, 2021)
The joint efforts in the fields of surgery, medicine and biomedical engineering, sponsored by both the government and the industry, have led to the development of mechanical support devices that can provide reliable circulatory support, which can temporarily support a patient’s circulation until either the heart recovers or until a new heart can be transplanted or permanently replace a failed heart. Their development has been driven by the shortage of donor organs. Various systems have eventually evolved for short or long-term support of patients suffering from cardiogenic and/or advanced heart failure (HF). Over time, several have been withdrawn from the market due to high rate of thromboembolism and pump-related complications, but many others remained with modern principles of circulatory support proved to be durable and reliable. Hopefully, the ever-evolving technology will yield several devices aimed at their miniaturization, with an energy supply without risk of infection, a system which is simple to implant and to exchange, minimalization of thrombus formation by optimal interior pump design, new antithrombotic medications and a system with demand-based pump activity. It is important to remember that such devices are only implanted to keep a patient alive or in an immediate life-threatening stage. In such circumstances, attribution of aforementioned difficulties to pump limitations or to advanced disease states remains difficult. In the coming years, ventricular assist devices (VADs) could be the most common surgical preference for treating severe HF.